Linear viscoelasticity and structure of polypropylene-montmorillonite nanocomposites - Rohlmann, Cora Otilia (2006)
Polypropylene (PP)/clay composites were prepared by melt mixing in a thermoplastic mixer using a polypropylene grafted with maleic anhydride (PPg) as the compatibilizer. Concentrations of an organophilic montmorillonite (MMT) between 2 and 15 wt% and concentration ratios of PPg/clay between 1:3 and 3:1 were employed to investigate the relationship between the structural characteristics of the hybrids and their rheological properties. The structure was analyzed with electron microscopy, X-ray diffraction and melt rheology. Thermogravimetric analysis and infrared spectroscopy were also used. The clay interlayer spacing increases after mixing with PP while the addition of PPg only facilitates the partial exfoliation of the clay platelets without changing that spacing. When clay loadings of 8 wt% or larger were used, an important fraction of the original clay particles was found to remain unmodified. The dynamic moduli show little effect of the presence of the inorganic material when no compatibilizer is added or the amount of PPg or clay is too small. As the extent of exfoliation increases, the linear viscoelastic behavior of the composites gradually changes with time while in the molten state, mainly at low frequencies. Evidence of solid-like behavior appears as the concentration of clay increases, for a given PPg/clay or PP/PPg concentration, or as the PPg concentration increases (for a given clay concentration). The concentrations of PPg and clay that induce percolation were observed to have an inverse relation. Evidence of regions with large concentration of MMT was obtained in the annealed samples of composites with solid-like rheological behavior. Additionally, infrared spectra of these materials suggest the simultaneous occurrence of chemical reactions between the PPg and the surfactant or products derived from its thermal decomposition during the annealing process.